The effect of the repurchase policy in stock tradingIn financial markets - case study - محمد, اياد طاهر (Journal of Economics and Administrative Sciences, 2011)
The research dealt with the case stock repurchase policy of Emaar Real Estate Company one of listed companies in Dubai Stock exchange. The research has launched from the cognitive dimensions of repurchasing policy which took great concern in the literatures of financial management, and also this policy became as substitute for distributing the monitory profit in the last three decades in the international financial markets, but it did not get any importance in the Arab Markets such as that of the Arab Gulf in addition to the Iraqi Stock Exchange.The research summarized a set of conclusions, the most important one was the consistence of analysis result with the test of the major two hypotheses (The first and third ones) , and the inconstancy  with the major second hypothesis. The most important recommendations is that the Boards of directors of the listed companies in the financial markets have to choose the most suitable timings for the announcement of the repurchasing policy and not restore to this policy during the financial crisis to limit the reduction of the market value of their stocks in financial market.